The role of the legal division of the Probolinggo regency secretariat in drafting local regulations - Amilia Putri K.S; Dita Dwi A.P; Efrilia Yusri; Lyra Nirmala; Malikal Bulqis; Natasatun Nadayah (Institute Of computer Science (IOCS), 2024)
This study aims to analyze the role, duties, and working mechanisms of the Legal Division of the Probolinggo Regency Secretariat in drafting Regional Regulations (Perda) to support the implementation of regional autonomy in accordance with Law Number 23 of 2014 concerning Regional Government and its amendments. The research method used is a normative juridical approach with a descriptive-analytical nature, based on a literature study of laws and regulations, official regional documents, and related academic literature. The results of the study show that the Legal Division has a strategic role in all stages of Perda formation, from planning, drafting academic papers, harmonization and legal review, to ratification and evaluation of implementation. The Legal Division serves to ensure the conformity of Perda with the national legal hierarchy and the needs of the local community. However, a number of obstacles were found, such as limited human resources, suboptimal inter-agency coordination, and low utilization of digital technology in the regional legislation system. Therefore, this study recommends increasing the capacity of legal officials, optimizing inter-agency coordination, and digitizing the regional legislation process so that the drafting of local regulations is more effective, transparent, and participatory.